¿How to study Interculturality from Design? There is no interculturality without creativity. (2019)
This article explores how to face the phenomenon of interculturality from research in the field of design. In the first part, the ways of research the area are described; then, the interculturality is defined from socio-cultural studies and communication with a critical approach. Additionally, some ways in which design practice has acted in spaces of cultural diversity are described, concluding that interculturality resides in multicultural creative systems; therefore, genuine interculturality cannot exist without collaborative creation in diversity.